Ethiopian Farmers use water harvesting techniques to fight climate change - International Livestock Research Institute (International Livestock Research Institute, 2013)
Water harvesting is one way that farmers can deal with climate-change induced water scarcity in Ethiopia. Here community members explain how this technology is used by households to grow high value crops when the rainy season is over. The photo film is produced by the project on “Enhancing communities’ adaptive capacity to climate-change induced water scarcity in drought-prone hotspots of the Blue Nile basin, Ethiopia” (a project implemented by ILRI, UNEP and Wollo university).